Analysis of integrated, quality and environment focused management practices in the Forage Industry Ltd, Bábolna - Kovács, Elza; Mészáros, János; Juhász, Csaba (Acta Agraria Debreceniensis, 2001)
The significance of the effect of agricultural activities on the environment was focused on later than that of industry; however, today, an increasing number of companies using an environmental management system (EMS) has been registered in this sector, too. In the agricultural sector, EMS according to ISO 14001 was introduced first in the forage industry by Bábolna Takarmányipari Kft. In our study, we analyze the environmental management system integrated into the quality system of this company and discuss the effects on the organization and the economic issues. As a result of the EMS, emissions have been reduced effectively, and both the responsibility system and technology have become more controlled. The company chose to develop its environmental performance continuously, which is proved to have been performed successfully, considering its limited, one-year experience.